Living Quran: Resepsi Komunitas Muslim Pada Alquran (Studi Kasus di Pondok Pesantren at-Tarbiyyatul Wathoniyyah Desa Mertapada Kulon, Kec. Astatana Japura, Kab. Cirebon) - Hilda Nurfuadah (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2017)
This article focuses on the study of the Living Quran as a reception for the Muslim community in the Koran. The Living Quran in its essence stems from the Quran phenomenon in Everyday Life, namely the meaning and function of the Koran that is truly understood and experienced by Muslim communities. The process of community interaction with the Koran is not only limited to the meaning of the text, but is emphasized more on the application (functional) aspects of the Qur'anic texts in daily life. Enabling the Qur'an as this arises because of the practice of interpreting the Koran which does not refer to the understanding of its textual messages, but based on the presumption of "fadilah" from certain parts of the Qur'an, the application of the Qur'anic texts then becomes an institutionalized tradition in people's daily lives.